Missão educacional alemã no Brasil: Irmãs Franciscanas - de Dillingen para a Baixada Fluminense: Duque de Caxias e São João de Meriti RJ (1937-1956) - Oliveira, Antoniette Camargo de (2012)
This work incorporates the research of the program of Post-graduate in education of the Universidade Federal de Uberlândia/MG and proposes understand the context of coming of the Franciscan sisters of Dillingen, from Germany for the Brazil, even as the reality of the education and of the schools that they created and keeps since 1940 and 1942 in the cities of São João de Meriti and Duque de Caxias, in Baixada Fluminense-RJ. However, this research begins since 1930, with the govern of Getúlio Vargas and the Reform Francisco Campos, where search show better the reality of the politics and of the education that preceded its arrival, at first in the city of Cabo Frio- RJ, since 1937 till 1956, with the formation of the first class of the Normal curse, offered by one of the colleges controlled by the referred sisters. Are addressed subjects how: the conflicts between Catholicism and escolanovismo, conservatism and liberalism, private and public, the problem of immigration living with nationalistic fervor; the educational reality of the Lowlands, which gained prominence mainly through the press duquecaxiense, the reality of today\'s College of St. Mary and St. Anthony with marked differences between the two, through specific documentation of both educational institutions, among others. But mostly we try to find possible traces or influences brought to the Brazilian education, through its Sisters/Teachers, \"form (ta) of\" in Germany, considering the Brazilian context and needs to adapt to it. To this end, it makes use of mainly obituaries of the sisters, in an attempt to generate evidence about the potential educational legacy here. The prevalence of elements inherent to Catholicism, such as the concept of Mission, the practice of catechizing, the existence of the Crusades and the distribution of Eucharistic \"Holy Cards\" is obvious in many of the documents. A unique experience, however, was to bring up the history of education in the suburbs, even through two private religious institutions and a German Catholic Congregation.